2019
DOI: 10.1523/jneurosci.1910-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Level of Consciousness Is Dissociable from Electroencephalographic Measures of Cortical Connectivity, Slow Oscillations, and Complexity

Abstract: Leading neuroscientific theories posit a central role for the functional integration of cortical areas in conscious states. Considerable evidence supporting this hypothesis is based on network changes during anesthesia, but it is unclear whether these changes represent state-related (conscious vs unconscious) or drug-related (anesthetic vs no anesthetic) effects. We recently demonstrated that carbachol delivery to prefrontal cortex (PFC) restored wakefulness despite continuous administration of the general ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
83
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(94 citation statements)
references
References 76 publications
(159 reference statements)
9
83
1
1
Order By: Relevance
“…4,12 However, recent evidence has suggested that the connectivity patterns fluctuate and frontoparietal connectivity does not strictly correlate with unresponsiveness in humans or rodents. 13,14,40 The current results speak in favour of local frontal connectivity measures and are in line with a study in non-human primates, where the repertoire of functional connectivity was shown to be constrained to structurally connected regions during anaesthesia and an increase in functional correlation within prefrontal areas was observed. 41 We focused on the broad alpha frequency band, and future studies should explore whether the long-range connectivity in frequencies outside the alpha bandwidth might reflect the behavioural state during constant dosing.…”
Section: Discussionsupporting
confidence: 90%
“…4,12 However, recent evidence has suggested that the connectivity patterns fluctuate and frontoparietal connectivity does not strictly correlate with unresponsiveness in humans or rodents. 13,14,40 The current results speak in favour of local frontal connectivity measures and are in line with a study in non-human primates, where the repertoire of functional connectivity was shown to be constrained to structurally connected regions during anaesthesia and an increase in functional correlation within prefrontal areas was observed. 41 We focused on the broad alpha frequency band, and future studies should explore whether the long-range connectivity in frequencies outside the alpha bandwidth might reflect the behavioural state during constant dosing.…”
Section: Discussionsupporting
confidence: 90%
“…They also highlight the need to carefully disentangle putative changes in network structure from effects induced by overall changes in correlation magnitude, or by the method of network construction; something that is likely to be difficult through the use of graph summary measures alone. We have not addressed the causal role of this muting, or whether it may simply mask structural network features underlying consciousness; although recent work (Pal et al 2020) suggests that anesthesia induced unconsciousness can be dissociated from the effects of anesthesia on the cortex, and so the relationship between consciousness and cortical information processing may be more complex than can be decoded from BOLD signal correlations alone.…”
Section: Discussionmentioning
confidence: 99%
“…For Integrated information theory, it turns out that a system with only bottom-up connectivity has no φ ('phi', the quantitative measure of consciousness on this theory; (Oizumi, Albantakis et al 2014): 19); Recurrent processing theory is based on the notion of backward, 'recurrent' processing; NCC studies in support of Global neuronal workspace theory suggests that consciousness is 'ignited' partly by recurrent connectivity; Higherorder thought and Metacognitive theories all operate with an assumption that some higher-level process can 'look down' at lower-level states; and finally, it is hard to see how Virtual reality theory would work without extensive top-down signalling in the construction of the internal virtual reality model that can arise in the absence of bottom-up signals. We also note that studies of the global state of consciousness in anaesthesia suggest that a global state of consciousness depends on top-down signalling in the brain (Boly, Garrido et al 2011, Boly, Moran et al 2012, Pal, Li et al 2020).…”
Section: Common Themesmentioning
confidence: 66%